Case Report: Rheumatoid arthritis patient with hip joint infection and acetabular protrusion undergoing total hip arthroplasty: a case study and literature review - Zhou, Jun; Zhou, Weijie; Wang, Peng; Zhang, Yinwei; Chu, Weitao; Fan, Jun; Lu, Hui (Frontiers in Surgery, 2025)
The chronic autoimmune disease rheumatoid arthritis (RA) affects primarily the synovial joints, leading to hip joint deformity and dysfunction manifestations such as acetabular protrusion and joint infection. We present the case of a female patient RA complicated by severe hip arthritis and acetabular protrusion syndrome. The disease progressed rapidly with elevated preoperative inflammatory markers, initially overlooking hip joint infection. The patient underwent total hip arthroplasty, and intraoperative synovial fluid bacterial culture revealed Gram-negative rod bacteria. Aggressive postoperative anti-infective therapy effectively controlled the infection. Therefore, early diagnosis and treatment of infections are particularly important.